دور التمويل الإسلامي في ترقية الإستثمار دراسة حالة الجزائر 2010-2021 - شويرب خيرة; شويرب وداد; حفاي عبد القادر (جامعة عمار ثليجي الاغواط, 2022)
This study deals with the role of Islamic finance in supporting and promoting investment in Algeria in general and at the level of Al Salam Bank in particular. Thus, this study aims to show role the position of Islamic finance, especially Islamic banking. in Islamic banks and the extent of its contribution to financing investments. We also tried to apply the study on Al Salam Bank Algeria During the period between (2011-2020). The study concluded that the Al Salam Bank Algeria relies on short-term financial instruments, represented in Murabaha in the first place, as it is a financial instrument that works to provide liquidity to a high degree and with lower risks, with low long-term investments, which constitute the latter. A limited percentage of the total volume of financing, and despite the contribution of the bank under study in promoting investment in Algeria, this contribution is still weak and did not live up to the level of aspirations compared to financing granted by traditional banks. Finally, this study recommended the necessity of developing Islamic financial institutions in Algeria and the necessity of Diversify its financial products, through the development of new contracts called composite or generated contracts, within the framework of Islamic financial engineering. in order to replace traditional investment financing with new alternatives in accordance with the principles of Islamic Sharia on the one hand, and the requirements of access to global financial markets on the other